Пошаговое объяснение:
Разделим одновременно числитель и знаменатель выражения
на n (n≠0):
1)
2) Находим значение полученного выражения при .
ответ:
Пошаговое объяснение:
Разделим одновременно числитель и знаменатель выражения
на n (n≠0):
1)![\frac{2m+n}{n-m}=\frac{(2m+n)n}{(n-m)n}=\frac{2m+n}{n}:\frac{n}{n-m}= \frac{2m+n}{n}*\frac{n-m}{n}=(\frac{2m}{n}+\frac{n}{n})*(\frac{n}{n}-\frac{m}{n} )=](/tpl/images/4515/1199/174aa.png)
2) Находим значение полученного выражения при
.
ответ:![\frac{11}{18}](/tpl/images/4515/1199/12e71.png)